A Study of Proper Saṅgha Dāna in Theravada Buddhism: A Study Based on Thai Buddhist Monks - Ukkhadhammo Phetkrai, Phra Rurngvit (The Journal of International Buddhist Studies College, 2023)
This research article wrote with 3 objectives in mind, namely 1) To examine the problems and impacts of Saṅgha Dāna in Thailand, 2) To examine the concept of Saṅgha Dāna in Theravada scriptures, 3) To present the proper Saṅgha Dāna for Buddhist Monks in Thailand. The finding shows various problems and impacts that aren’t so difficult or complicated to solved if Thai Buddhists society pay attention and willing to co-operate. The original teaching on Saṅgha Dāna practice in the Tipitaka is found to be the offering given to group of the Ariya monks (the 4 pairs of individuals, the Stream Enterer for instance) of at least 4 members. However, with the right intention and appointing, it is merely the Dāna offering for the sake of Saṅgha even though the offeror only give to a single monk or appointed individual. The results founded have been used to present the ideal proper Saṅgha Dāna for the contemporary Thai Buddhist society in the following categories. Proper materials for Saṅgha Dāna must be consumableand good quality. Proper monks must be ariya (noble) monks of at least 4 members, otherwise the monks should at least complete with vijjā carana sampanno (endowed with perfect clear vision and exemplary good conduct). Proper offeror should have a good virtue and characteristics. The proper occasion to offer Saṅgha Dāna is the monks are visiting, leaving, ill, goods are hard to get and still fresh and new. Proper understanding is when realized that most of the modern days Saṅgha Dāna practices are not what originally taught by the Buddha.